1979
DOI: 10.1136/jcp.32.10.1003
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoreactive trypsin concentration after a Lundh meal. Its value in the diagnosis of pancreatic disease.

Abstract: SUMMARYThe changes in serum trypsin concentration have been measured in 47 subjects for up to 2 hours after a Lundh meal. In 18 healthy controls, mean fasting trypsin concentration was 285 +125 ng/ml (mean ±2 SD). The maximum increase after the Lundh meal (the trypsin response ratio) was 6-7±7-5 %.Six patients with chronic renal failure had elevated fasting serum trypsin concentrations (range 460-1100 ng/ml) but trypsin response ratios fell within the control range.Of five patients with relapsing pancreatitis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…Our normal range for healthy controls (117-637 ,tg/l) is appreciably wider than ranges found in previous studies using the same radioimmunoassay,2 4 12 but only one study2 investigated a comparable number of subjects. There are several possible reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 57%
“…Our normal range for healthy controls (117-637 ,tg/l) is appreciably wider than ranges found in previous studies using the same radioimmunoassay,2 4 12 but only one study2 investigated a comparable number of subjects. There are several possible reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the finding of subnormal serum concentrations of TLI and pancreatic isoamylase provides evidence for impaired pancreatic exocrine function (12, 13). In healthy subjects, food has no influence on serum levels of TLI and pancreatic isoamylase (15,20) and, in accordance with this, we found no change in these concentrations in the diabetics after breakfast and insulin. The lacking relationship between serum concentrations of TL1 and pancreatic isoamylase and known duration of diabetes and daily insulin dose in our investigation is in agreement with several studies of duodenal pancreatic outputs of enzymes in diabetes and the above mentioned variables (3, 5, 10, 22).…”
Section: Discussionsupporting
confidence: 84%
“…Serum trypsin may be normal or subnormal in chronic pancreatitis (Elias et al ., 1977). [7] Previous studies have revealed that exocrine insufficiency is invariably associated with a low trypsin concentration,[1516] but a normal concentration has been reported. [17] However, increased levels observed in the present study in CP compared to controls suggests that proteolytic activity of trypsin on pancreas may result in the cascade of events which further results in the activation of other proteases with subsequent cell damage.…”
Section: Discussionmentioning
confidence: 99%